2015
DOI: 10.3748/wjg.v21.i12.3599
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis for hepatocellular carcinoma with transarterial chemoembolization pre-transplantation: Retrospective analysis

Abstract: TACE pre-LT for HCC patients increased the chances of pulmonary or distant metastasis of the primary tumor, thus reducing the long-term survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…It is worried that if tumors cannot achieve complete pathological response after chemoembolization, the residual intrahepatic tumor cells may develop resistance toward chemotherapeutic agents and become more invasive than those receiving no TACE treatment. [27,28] The intratumoral necrosis induced by TACE may weaken the adhesive potential of the tumor and subsequently facilitate the release of cancer cells from the primary tumor and dislodgment into the bloodstream, thus increasing the risk of postoperative recurrence. [29] Our study showed that: for patients from mean tumor diameter >5 cm subgroup, the complete necrosis rate was all below 20%.…”
Section: Discussionmentioning
confidence: 99%
“…It is worried that if tumors cannot achieve complete pathological response after chemoembolization, the residual intrahepatic tumor cells may develop resistance toward chemotherapeutic agents and become more invasive than those receiving no TACE treatment. [27,28] The intratumoral necrosis induced by TACE may weaken the adhesive potential of the tumor and subsequently facilitate the release of cancer cells from the primary tumor and dislodgment into the bloodstream, thus increasing the risk of postoperative recurrence. [29] Our study showed that: for patients from mean tumor diameter >5 cm subgroup, the complete necrosis rate was all below 20%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete necrosis rate of tumors after TACE is only 10-20% [26]. Additionally, the possibility of recurrence and metastasis of residual HCC cells increases after TACE [27]. Increased plasma insulin-like growth factor-2 levels after TACE appear to be associated with the occurrence of metastatic HCC after TACE [5].…”
Section: Discussionmentioning
confidence: 99%
“…Two reviewers reached an agreement on the finally included studies. A total of 2902 patients (TACE plus LT: 721 LT: 2181) from 7 retrospective cohort studies and 5 case control studies were included in the qualitative synthesis, [19][20][21][22][23][24][25][26][27][28][29][30] no randomized controlled trial was found. The essential characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%